Building on the Ccr4‐Not architecture. (22nd August 2016) - Villanyi, Zoltan; Collart, Martine A.
Abstract : In a recent issue of Nature Communications Ukleja and co‐workers reported a cryo‐EM 3D reconstruction of the Ccr4‐Not complex from Schizosaccharomyces pombe with an immunolocalization of the different subunits. The newly gained architectural knowledge provides cues to apprehend the functional diversity of this major eukaryotic regulator. Indeed, in the cytoplasm alone, Ccr4‐Not regulates translational repression, decapping and deadenylation, and the Not module additionally plays a positive role in translation. The spatial distribution of the subunits within the structure is compatible with a model proposing that the Ccr4‐Not complex interacts with the 5′ and 3′ ends of target mRNAs, allowing different functional modules of the complex to act at different stages of the translation process, possibly within a circular constellation of the mRNA. This work opens new avenues, and reveals important gaps in our understanding regarding structure and mode of function of the Ccr4‐Not complex that need to be addressed in the future. Abstract : The structure of the Ccr4‐Not complex reveals that mRNA decay components interact with one side of the complex. The other side is available to contribute to co‐translational processes. This might ensure a direct physical link between translation and mRNA decay processes, particularly if the mRNA is in a circular constellation.